Os Paresí - Wáimare e o uso de plantas medicinais, Mato Grosso (Brasil) - Morais, Rosa Mari Guimarães Godinho de (1998)
The current study refers to the Paresí Indians, subgroup - Wáimare – of the Aruak linguistic trunk – and took place on the indigenous territories of Tirecatinga and Utiariti, in the state of Mato Grosso, Brazil. The emphasis refers to the knowledge of this subgroup about medicinal plants and their utility in the “healing” process. The information was collected through field studies, with sample botanical specimens explaining their therapeutic usefulness. The qualified figures were obtained, above all, between the “old ones”of the field of knowledge, with the help of bilingual translators. There were identified 90 botanical specimens pertaining to 41 families, distributed in the savannah vegetation (58%), ciliar - forest (24%), new scrub growth of cleared land (12%), and low cultivated plain (3%). The therapeutic feature most often used was a bath with 49% using the whole plant in physical therapy, and 29% separating and using the leaves in the making a of tea. Of the various ailments portrayed, those that occurred most often were headache, itching, body aches, wounds, and swelling or bloating, etc. These figures are based on daily information of this subgroup and their traditional practices.